Risperidone Pellets, Pycnogenol®, and Glucomannan Gummy Formulation for Managing Weight Gain and ADHD in Autistic Children - Rawand M. Daghmash; Mai S. Khanfar; Ruba S. Darweesh (MDPI AG, 2024)
Gummy formulations are defined as gradually or slowly released solid oral dosage forms. Risperidone is an atypical antipsychotic medication used to treat schizophrenia and autism-related irritability. This study presents the development of visually appealing, patient-tailored medicated gummies that act as a novel pharmaceutical form of Risperidone for pediatrics. In this study, two gummy bases were used, one containing Glucomannan and the other containing Gelatin as a gelling agent, where these gummy bases were loaded with coated Risperidone pellets with a controlled release layer. The final products were evaluated for their pH, viscosity, content uniformity, drug content, and dissolution profile. Both formulas showed proper rheology and met content and weight uniformity standards. The release rates for F1 and F2 in the acidic media were 25% and 11%, respectively, after 2 h. At the same time, a full-release profile for Risperidone was noticed in both formulae at pH 6.8 where the release lasts for 24 h. It can be concluded that the chewable semi-solid dosages (gummies) filled with coated pellets are suitable for pediatric patients since pediatrics have drug-related problems which can be solved using high gastro-resistance coated pellets, which also shows a proper release profile for the drug.